The Challenge of Migration: Schooling the Second Generation in Europe - FAAS, DANIEL (My University, 2010)
In several European countries, 10% or more of the student population now has a migrant background; and some countries are facing this phenomenon for the very first time. There is growing concern that students with an immigrant background perform lower than their native peers. Dealing effectively with the increasing migration-related diversity in schools, and in society at large, thus presents challenges. Nations in Europe differ considerably in their responses. For example, in Greece, for a school to be classified as intercultural, at least 45% of its student population must be non-Greek, but not all schools which pass this threshold are classified as intercultural. In Germany, `integration? has become a policy buzzword but the country is still struggling to leave behind the image of the third-generation `foreigner? (Auslander) or `foreign citizen? (auslandische Mitburger). In Britain, we have witnessed a rethinking of multiculturalism which led to the emergence of `community cohesion? as a public agenda alongside promoting global citizenship. Schooling in Ireland, by contrast, is shaped by the Catholic Church regarding enrolment policies and curriculum content.
PUBLISHED
Policy brief disseminated to European Commission, Council of Europe, OECD and national governments across Europe
Keywords: Migration; Policy; Europe; Education; Identities in Transformation; Inclusive Society; International Integration